Case Study: The Neutrinos That Challenged Einstein: A critical reflection on the OPERA neutrino anomaly and its scientific (JOURNAL OF ADVANCES IN PHYSICS, 2026)
In 2011, the OPERA experiment reported that neutrinos appeared to travel faster than light, a claim that momentarily shook the foundations of modern physics before being retracted as an instrumental error. This episode, known as the “neutrino anomaly,” remains a remarkable case study in how science reacts to results that challenge established paradigms. Thirteen years later, this reflective essay revisits the event to explore its epistemological and ethical implications, raising questions about the boundaries between scientific caution, institutional pressure, and the human dimension of discovery. Far from being an accusation, this analysis aims to highlight the enduring value of transparency, doubt, and humility in experimental science.